Effectiveness Analysis of Fiscal Financial Statement Preparation in Minimizing Tax Risk - Hasinggaan Jhon Babtista Tamba; Dinda Atika Sari; Hidayana Sa’adah; Titus Pasaribu; Asri Rama Gita Rangkuti (CV. AFDIFAL MAJU BERKAH, 2025)
Fiscal policy is a primary instrument for the government in managing the economy through the regulation of state revenue and expenditure. This article aims to analyze the role of basic fiscal policy in economic stabilization, long-term growth, and the challenges of its implementation in identifying effective fiscal policies to control inflation and budget deficits. However, factors such as time lag, political uncertainty, and government debt pose significant challenges. This article also highlights the importance of coordinating fiscal policy with monetary policy to achieve optimal macroeconomic objectives.The largest source of state revenue comes from taxes, including Corporate Income Tax (CIT) levied on a company's annual income. The term 'badan' (entity) encompasses entities such as limited liability companies, state-owned enterprises, regionally-owned enterprises, cooperatives, foundations, and others. This system increases administrative efficiency and reduces the government's burden but requires strict oversight to prevent tax avoidance.Research findings indicate that tax risk management is not only crucial for mitigating potential financial losses and ensuring legal compliance but also for enhancing tax administration efficiency and optimizing tax strategies. . Furthermore, this study reveals various challenges encountered in the implementation of risk management. This research analyzes the effectiveness of preparing fiscal financial statements in minimizing tax risks, focusing on the differences between commercial and fiscal financial statements, particularly regarding the recognition of expenses and the depreciation of fixed assets. Fiscal corrections are necessary to ensure that the reports comply with Law No. 36 of 2008 on Income Tax. Using a qualitative descriptive method, the study finds that although the preparation of fiscal corrections has adhered to regulations, there are still several expense components that need to be corrected. These corrections impact the increase in taxable income and the amount of tax owed. The research results emphasize the importance of accurate fiscal corrections in supporting tax compliance and minimizing tax risks within a self-assessment system